A user's guide to performance of the best shoulder physical examination tests. Issue 14 (15th January 2013) - Myer, Cortney A; Hegedus, Eric J; Tarara, Daniel Thomas; Myer, Daniel M
Abstract : Background: This article provides clinicians with a user's guide on the performance of the shoulder physical examination tests most supported by current evidence from a recent systematic review published in the British Journal of Sports Medicine . Discussion: A description of clinical shoulder tests is provided with explanations on exact testing procedures and complimentary photographs.